THE STRATEGIC ROLE OF PUBLIC RELATIONS IN DEVELOPING A POSITIVE IMAGE OF ANWARUS SALAF SEMPULANG PONPES AS AN EDUCATIONAL OPTION - Firmansyah, Ahmad; Zamroni, Zamroni (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research explores the strategic role of public relations in developing a positive image of the Anwarus Salaf Sempulang Islamic Boarding School as an educational choice. With a qualitative approach, research was carried out through interviews, observations and document analysis to explore the communication strategies implemented by public relations in building trust and attracting public interest and increasing the number of new students. The research results show that the use of digital media, traditional approaches, and active community involvement are the keys to success in promoting superior Islamic boarding school programs. Apart from that, traditional activities such as Qiroatul Polar performances and community service also strengthen the image of Islamic boarding schools. Challenges such as limited resources and negative perceptions were successfully overcome through program innovation based on Islamic values and technology integration. In conclusion, public relations has a vital role in creating the image of Islamic boarding schools that are not only relevant but also highly competitive as Islamic educational institutions today.